Synthesis of onboard array antennas including interaction with the mounting platform and mutual coupling effects. - Obelleiro, F.
The synthesis of array antennas mounted on ships, or any other vehicular platform, is addressed here. Both the mutual coupling between the array elements, and their interaction with the mounting platform, are considered and introduced into the synthesis procedure. This is done by using a three-dimensional formulation of the method of moments, which models the currents induced on the platform and the antennas, combined with an optimization procedure. Some results are presented, illustrating the capability of the proposed synthesis method.
Keywords: Antenna radiation patterns; Conformal antennas; Aircraft antennas; Antenna arrays; Antenna proximity factors; Aircraft antennas; Vehicular antennas; Electromagnetic compatibility; Method of Moments